Optimization of Preparation of Bioactive Peptide by Enzymatic Hydrolysis in Katsuwonus pelamis Using Response Surface Methodology and its Anti-fatigue Effect on Mice - LI Shoujiang; KONG Xiangjia; LIU Zhiyu; ZHAO Feng; SU Yongchang; CHEN Xiaoting (康复学报)
ObjectiveTo optimize the enzymatic hydrolysis technology of bioactive peptide in Katsuwonus pelamis and observe the anti-fatigue effect of bioactive peptide on mice.MethodsWith the yield of bioactive peptide in Katsuwonus pelamis as the evaluation index, the papain, neutral protease, flavor protease, alkaline protease and acid protease were used to screen out the best enzymes for Katsuwonus pelamis surimi. The effects of solid-liquid ratio, enzyme amount, enzymatic reaction time and temperature on the enzymatic hydrolysis were investigated. The response surface methodology was designed based on the single factor experiment to obtain the optimal enzymatic hydrolysis condition of bioactive peptide in Katsuwonus pelamis. The fatigue mice model was established by incremental loaded swimming training and the experiment mice were randomly divided into quiet blank group, exercise model group, positive control group, low-, medium- and high-dose of bioactive peptide in Katsuwonus pelamis groups (200, 400, 800 mg/kg, respectively) according to the body mass. Except for the quiet blank group, the other groups were trained with incremental loaded swimming with the training time as the variable. The loaded swimming test was conducted to detect the exhaustion time of mice. The contents of serum urea nitrogen (BUN) and serum lactic acid (LD), serum lactic dehydrogenase (LDH) activity, liver malondialdehyde (MDA) content and liver superoxide dismutase (SOD) activity were measured with corresponding kits.Results1) The yield of bioactive peptide in Katsuwonus pelamis hydrolyzed by flavor protease was statistically higher than that of neutral protease, papain, alkaline protease and acid protease (P<0.01 or P<0.05). When the solid-liquid ratio was fixed at 1∶1 (g/mL), the optimal conditions of flavor protease hydrolysis were enzyme amount 4 400 U/g, enzymatic time 6.5 h and temperature 42 ℃. Under these conditions, the yield of bioactive peptide in Katsuwonus pelamis was 33.166%. 2) The contents of BUN, LD, MDA, and the activities of LDH, SOD in the exercise model group were significantly higher than those in the quiet blank group (P<0.01). Compared with the exercise model group, the exhaustion swimming time of the positive control group, low-, medium- and high-dose of bioactive peptide in Katsuwonus pelamis groups were significantly prolonged (P<0.01), the contents of serum BUN, serum LD and liver MDA, and serum LDH activity were decreased (all P<0.01), while the liver SOD activity was improved (P<0.01).ConclusionThe response surface methodology was used to determine the optimal enzymatic hydrolysis technology of bioactive peptide in Katsuwonus pelamis with flavor protease, which verified that bioactive peptide in Katsuwonus pelamis could relieve fatigue in exhausted swimming mice.